Motivasi Bercadar Mahasiswi Umsurabaya Dalam Perspektif Majelis Tarjih Muhammadiyah - Mulyono Mulyono (Universitas Muhammadiyah Surabaya, 2019)
ABSTRACTThis research is motivated by the presence of several students of UMSurabaya who wear Hijab/long veils. This phenomenon raises a different perspective on the social environment, both from female students who wear the hijab and students who do not wear hijab. In this study, there are two formulation of the problems including: What is the Motivation of students in UMSurabaya wearing hijab? What is the perspective of the decision of Tarjih Muhammadiyah toward the motivation of student in UMSurabaya on wearing hijab? This study aims to determine the motivation of students in UMSurabaya who wear hijab and how is the perspective of Tarjih Muhammadiyah Decision on students’ motivation on wearing hijab in UMSurabaya.The type of this research is a field qualitative research. The primary data is collected through interviewing students who wear hijab and Academision in UMSurabaya, as well as some Figure of Tarjih Muhammadiyah Surabaya. The secondary data are obtained from the literature about hijab. After the data are collected, then it is analyzed qualitatively and described in descriptive form.The results of this study concludes that the motivation of students of UMSurabaya who wear hijabis more influenced by their own internal factors. They want to try to correct themselves and avoid slanders. Whereas, based on the decision of Tarjih Muhammadiyah, motivation of students of UMSurabaya does not contradict to the Muhammadiyah perspective. However, in the Assembly of Tarjih Muhammadiyah doesn’t give appeal in wearing the hijab because wearing the hijab depends on the rights of each individual Muslim woman. Keywords: hijab, the Assembly of Tarjih Muhammadiyah, UMSurabaya.